การนำเสนอข่าวเกี่ยวกับพระสงฆ์ในหน้าหนึ่งของหนังสือพิมพ์รายวัน กับการเปิดรับข่าวสารและความเชื่อมั่นทางศาสนาของประชาชน - สุจิตรา เหลืองชูเกียรติ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this research is to study the news presentations concerning buddhist monks on front page of "Kao Scd" newspaper, the relation between newspaper to the religion belief of people and the relation between other factors (families, friend, lecturer occupation, financial status, religion-oriented and other medias) to the religion belief of people. The methodology of this study was a quantitative analysis by analyse the content of "Kao Sod" news presentation and a survey research from a focus grou who are buddhism and "Kao Sod" reader. SPSS programe was used to calculate and analyse. This survey and analysis shows that "Kao Sod" newspaoer presented a negative aspect of buddhist monks. The news exposure of people on "Kac Sod and other factors (families, friend, lecturer, occupation, financial status, religion-oriented and other medias) are related to the belief of people. This is to say that people who expose to a newspaper has influence on the religions belief of people as well. On the other hand, the study shows that even the news presentation of "Kao Sod" which show the negative aspect of ouddhist monks has no influence on the religions belief of people.